Seismic Behavior of Low Earthquake-Resistant Arch-Shaped Roof Masonry Houses Retrofitted by PP-Band Meshes - Sathiparan, N.; Meguro, K. (My University, 2012)
This paper introduces a technically feasible and economically affordable PP-band (polypropylene band) retrofitting for low earthquake-resistant masonry structures in developing countries. Results of the basic material tests and shaking table tests on building models show that the PP-band retrofitting technique can enhance safety of both existing and new masonry buildings even in worstcase scenarios of earthquake ground motion as in the Japan Meteorological Agency (JMA) seismic intensity scale 7. Therefore, the proposed method can be one of the optimum solutions for promoting safer building construction in developing countries and can contribute to earthquake disaster mitigation in the future. DOI: 10.1061/(ASCE)SC.1943-5576.0000113. © 2012 American Society of Civil Engineers.
Keywords: Earthquake engineering; Masonry